Nitrogen assisted etching of graphene layers in a scanning electron microscope - COLEMAN, JONATHAN; FOX, DANIEL; O'NEILL, ARLENE; ZHOU, DAN; ZHANG, HONGZHOU (My University, 2011)
We describe the controlled patterning of nanopores in graphene layers by using the low-energy (<10?keV) focused electron beam in a scanning electron microscope. Regular nanometer-sized holes can be fabricated with the presence of nitrogen gas. The effect of the gas pressure, beam current, and energy on the etching process are investigated. Transmission electron microscopy, coupled with plasmon energy loss imaging, reveals the microstructure modification of the etched graphene. A nitrogen-ion assisted etching mechanism is proposed for the controlled patterning.
PUBLISHED
Keywords: Condensed matter physics; Graphene; Nanoscience & Materials